Response of Fressia hybrida plant to spraying with liquid universal fertilizer and Salicylic acid in growth parameters - Abbass, Jamal Ahmed; AL-Zurfy, Mushtaq Talib Hammdi; Mohmmed, Hawraa Kameel (Sulaimani Journal for Pure and Applied Sciences, 2018)
An experiment was conducted at the lath house of Agriculture Faculty \Kufa University during the growing seasons of 2015-2016 to study the response of freesia plant to spraying liquid universal fertilizer and salicylic acid on growth parameters. Experiment was adopted a Randomized Complete Block Design (R.C.B.D) with three replicates in two factors. First three concentration of spraying liquid universal fertilizer i e.(0, 3 and 6)ml.L-1. Second three concentration of Salicylic acid i.e.(0, 40and 80)mg.L-1. Means were compared by using the Least Significant Difference (L.S.D.) test at probability 0.05 Results showed that spraying liquid universal fertilizer at a concentration 6ml.L-1 and Salicylic acid at a concentration of 40mg.L-1 significantly increased the number of leaves per plant, shoot dry weight, number of inflorescence per plant, inflorescence stalk length, diameter of inflorescence stem, number of florets per inflorescence, diameter of florets, floret dry weight to 7.33 leaf.plant-1, 5.15g, 7.33 inflorescence. plant-1, 42.03cm, 5.43mm, 13.33mm,7.93cm and 3.10g respectively, and decrease the number of the days until opening the first flower bud to 140.60days. Spraying liquid universal fertilizer at a concentration of 6ml.L-1 and Salicylic acid at a concentration of 80mg.L-1 significantly increased the content of total chlorophyll and carbohydrates to 41.77mg.100g-1fresh weight and 13.43mg.100g-1 dry weight, , compared to the control treatment which gave the lowest vales (3.66 leaves.plant-1, 2.37g, 3.33inflorescence. plant-1, 30.13cm, 1.60mm, 6.33floret. inflorescence-1 ,3.36cm and 1.08g, 35.11mg.100g-1 fresh weight, 7.50mg.100g-1 dry weight respectively), and increased the days until opening the first flower bud to 169days.
Keywords: Fressia hybrida plant; liquid universal fertilizer; Salicylic acid